Proceedings of the 11th International Congress on the Archaeology of the Ancient Near East: Vol. 1: Mobility in the Ancient Near East. Images in Context. Archaeology as Cultural Heritage. Engendering Near Eastern Archaeology. Societal Contexts of Religion. Shaping the Living Space - Otto, Adelheid; Herles, Michael; Kaniuth, Kai (Proceedings of the International Congress on the Archaeology of the Ancient Near East, 2020)
Cover -- Title Pages -- Contents of Vol. I -- Editors' Foreword -- Welcoming address to the 11th ICAANE in Munich, April 3, 2018 -- Welcoming speech on the occasion of the opening of the 11th ICAANE Munich, April 3rd 2018 -- Section 1: Mobility in the Ancient Near East -- Mobility in the Ancient Near East: Themes, Issues, Challenges -- Cooking Pots in Iron Age II Judah:A Confined or Mobile Distribution? -- Achaemenid-time Glass Vessels from Lori Berd (Armenia) -- The Mobility of Syrian Culture to Assyria during the Neo-Assyrian Period -- Neither Diffusion of Ideas nor Simple Trade of Objects: The Moving of Specialized Canaanean Blade Knappers during the Early Bronze Age in the Southern Levant -- Mobility Between the South Caucasus and the Near East: Cultural Interaction of Early and Middle Bronze Age Societies -- The Husking Tray: A Shared Cooking Technology between the Late Neolithic Communities of the Near East? -- Obsidian on the Move: From the Sources to the Tool. The Case of Tepeçik-Çiftlik (Turkey) around 6000 BC -- Roads around the Sea of Galilee from the Neolithic to the Persian Period -- Section 2: Images in Context -- The Winged Disc in Mesopotamia -- The Multiplicity of Ancient Near Eastern Storm-Gods in the Visual Record -- The Multiform Power of Visual Communication and its Reception. Some Suggestions from the Documentation of Mesopotamia -- Beyond Ornamentation: Contextualizing Research of Personal Adornment in the Ancient Near East -- A Demon's Travel Kit. An Introduction to the Items Depicted on Amulets against the Demoness Lamaštu -- Symbol of the Sun -- The Terracotta Figurines of Tell Halaf in the Hellenistic Period. Between Continuity and Change -- Images in Context: The Interpretation of Weather God Imagery -- Flaying the Enemy in Assyria. A Brief Study on Neo-Assyrian Archaeological and Textual Evidence.